Severe Intrapartum Asphyxia from Subamniotic Hemorrhage. (1st November 2016) - Lo, Tsz-Kin; Lee, Andrea; Chan, Wan-Pang; Hui, Sze-Ki; Fu, Yu-Ming; Shek, Chi-Chiu; Lam, Angus
ABSTRACT: Subamniotic hemorrhage results from rupture of chorionic vessels near the cord insertion. In the literature, it has never been a major cause for severe intrapartum complications. We report the first case of acute massive subamniotic hemorrhage intrapartum resulting in severe perinatal asphyxia.